Substrate-mediated regulation of the arginine transporter of Toxoplasma gondii. - Esther Rajendran (Public Library of Science (PLoS), 2021)
Intracellular parasites, such as the apicomplexan Toxoplasma gondii, are adept at scavenging nutrients from their host. However, there is little understanding of how parasites sense and respond to the changing nutrient environments they encounter during an infection. TgApiAT1, a member of the apicomplexan ApiAT family of amino acid transporters, is the major uptake route for the essential amino acid L-arginine (Arg) in T. gondii. Here, we show that the abundance of TgApiAT1, and hence the rate of uptake of Arg, is regulated by the availability of Arg in the parasite's external environment, increasing in response to decreased [Arg]. Using a luciferase-based 'biosensor' strain of T. gondii, we demonstrate that the expression of TgApiAT1 varies between different organs within the host, indicating that parasites are able to modulate TgApiAT1-dependent uptake of Arg as they encounter different nutrient environments in vivo. Finally, we show that Arg-dependent regulation of TgApiAT1 expression is post-transcriptional, mediated by an upstream open reading frame (uORF) in the TgApiAT1 transcript, and we provide evidence that the peptide encoded by this uORF is critical for mediating regulation. Together, our data reveal the mechanism by which an apicomplexan parasite responds to changes in the availability of a key nutrient.